Comparing children and parental preferences for active commuting to school. A focus on Italian middle-school students. (March 2023) - Rotaris, Lucia; Del Missier, Fabio; Scorrano, Mariangela
Abstract: Active commuting to school has significant positive health and environmental impacts; however, the increasing use of private vehicles has transformed school commuting from an active to a passive activity. Our research is aimed at analyzing which factors influence the choice on how to commute to school with a special focus on the role played by the Covid-19 health emergency. We carried out an online survey involving a sample of 193 students of a middle school of Trieste (Italy) and 217 parents. We find that attitudes and perceptions of children and parents significantly differ with respect to both the risks and benefits of different means of transportation and with respect to the policies that should be implemented to support active commuting to school. Our study is innovative with respect to the age range we focused on, since most of the literature deals with young children (elementary school) or with adolescents (high school) whose modal choice are taken either by their parents or by the students themselves. With reference to middle school students, instead, it is expected that children and parents jointly take the choice on how to commute and it is relevant to detect the role played by each family member in the decision-making process. Our results will be useful to local administrators, policy-makers and decision-makers in order to design, implement and support transport and demand management policies that are effective in shifting the mobility habits of middle school students toward healthier and more sustainable means of transportation.